Recommentions for evaluation and treatment of congenital cytomegalovirus infection (Archives of Pediatrics of Uruguay, 2025)
Congenital cytomegalovirus (CMV) infection is the most common congenital viral infection.It produces important long-term sequelae such as sensorineural deafness and psychomotor delay, with timely diagnosis and early antiviral treatment could be reduced.The development of national or local guidelines for the systematic approach of this pathology in both pregnant women and fetuses, as well as in the newborn, is essential to improve perinatal and long-term results, but also for health professionals to become aware of the importance of this pathology.This document summarizes your diagnosis, clinical follow-up and treatment.
Keywords: Cytomegalovirus Infections; Infection/congenital